Coil embolization of artery in advance endoscopic necrosectomy for walled‐off necrosis can prevent arterial bleeding. Issue 1 (8th November 2020) - Honta, Shunsuke; Hayashi, Tsuyoshi; Katanuma, Akio
Abstract : Watch a video of this article